Inflation and financial development: Evidence from Brazil - Manoel Bittencourt (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2008)
We examine the impact of inflation on financial development in Brazil and the data available permit us to cover the period between 1985 and 2002. The results – based initially on time-series and then on panel time-series data and analysis, and robust for different estimators and financial development measures – suggest that inflation presented deleterious effects on financial development at the time. The main implication of the results is that poor macroeconomic performance has detrimental effects to financial development, a variable that is important for affecting, for example, economic growth and income inequality. Therefore, low and stable inflation, and all that it encompasses, is a necessary first step to achieve a deeper and more active financial sector with all its attached benefits.
Keywords: E31; E44; O11; O54; 330; financial development; inflation; Brazil; Inflation; Finanzsektor; Entwicklung; Brasilien